N-Heterocyclic Carbene-Organocatalyzed Arene Formation: Application in Atroposelective Synthesis of Polysubstituted Benzenes - Xu, Ke; Wang, Ziyuan; Zhu, Tingshun (Synlett, 2020)
In recent decades, organocatalysis by N-heterocyclic carbenes (NHCs) has emerged as a versatile and powerful method in organic synthesis. As a result of the power of NHC organocatalysis to produce cyclic compounds, polysubstituted benzenes, which are among the most important cyclic compounds in organic chemistry, can be synthesized efficiently and selectively. This article briefly summarizes the history of NHC organocatalysis, including recent developments in benzene-formation methods, and highlights our recent work in atroposelective arene formation by carbene-catalyzed formal [4+2] cycloadditions. We expect that more NHC-catalyzed methods for the synthesis of asymmetric arenes will be developed in the near future, providing shortcuts to syntheses of sophisticated chiral functional molecules with polysubstituted benzene nuclei.
Keywords: N-heterocyclic carbene; arenes; atroposelectivity; cycloaddition; asymmetric catalysis